ChatGPT: Opportunities and Challenges in the Learning Process of Arabic Language in Higher Education - Lelepary, Heppy Leunard; Rachmawati, Rima; Zani, Benny Novico; Maharjan, Kailie (Journal International of Lingua and Technology, 2023)
Today there are no more people who do not know about technological developments. Everything is very sophisticated and modern. In fact, it is very easy for someone to know something through technology-based media and fast in disseminating various information. All of this is of course thanks to increasingly advanced technology. As recently appeared an application called Chat GPT. GPT Chat is an application that can respond to every question asked by respondents. Chat GPT stands for "Chat-based Generative Pre-trained Transformer". GPT chat is also a language model developed by Open AI that uses the powerful transformers architecture to generate responsive and context-appropriate text conversations. GPT Chat has been widely used by all groups, especially in the world of education. GPT Chat can be used by students in learning Arabic in tertiary institutions such as to improve their skills in kalam and qiraah. The purpose of this study is to find out that the use of gamification in learning Arabic has an influence on students' qiraah skills and also makes it easier to complete assignments. The data collection technique is through the distribution of a questionnaire. In the questionnaire there are statements that will be answered by students in tertiary institutions. The results of this study explain that the use of Char GPT in learning Arabic in tertiary institutions gets a positive response from students such as increasing students' reading skills, increasing motivation in learning, increasing enthusiasm for learning, and making it easier to complete assignments. The conclusion of this research explains that the existence of GPT Chat provides enormous opportunities, especially in the process of learning Arabic because there are many benefits obtained from using GPT Chat. The limitation of this research is that researchers only conduct this research at the tertiary level which incidentally has the ability to think critically.